STRAIN PARTITIONING AND STRESS ROTATION AT THE NORTH ANATOLIAN FAULT ZONE FROM AFTERSHOCK FOCAL MECHANISMS OF THE 1999 IZMIT MW = 7.4 EARTHQUAKE - Bohnhoff M.; Grosser H.; Dresen G. (My University, 2006)
We investigate aftershock focal mechanisms of the Mw=7.4 Izmit earthquake of 1999 August 17, on the western North Anatolian fault zone (NAFZ). Spatial clustering and the orientation of 446 fault plane solutions are analysed. The Izmit mainshock occurred as a right-lateral slip on an EW-trending near-vertical fault plane. Aftershock clusters define four individual fault segments. Focal mechanisms surrounding the epicentres of the Izmit and subsequent Düzce mainshock (Mw= 7.1, 1999 November 12) indicate predominantly strike-slip but also normal faulting. Aftershocks in the area between the Izmit and Düzce segments are mainly related to EW-oriented normal faulting delineating a small pull-apart structure. Beneath the easternmost Sea of Marmara, alignments of aftershocks suggest branching of the NAFZ into three or more active segments that differ significantly in terms of their focal mechanism characteristics. The distribution of aftershock focal mechanisms corresponds to fault segmentation of the NAFZ in the Izmit-Düzce region produced by coseismic slip. Areas with large amounts of coseismic slip show aftershocks that are predominantly strike-slip, but low-slip barriers show mostly normal faulting aftershocks. Stress tensor inversions of the aftershock focal mechanisms show rotations of the local stresses following the Izmit mainshock. In the Izmit-Sapanca area, the maximum horizontal compressive stress axis is horizontally rotated counter-clockwise by 8° with respect to the coseismic and long-term regional stress field. Towards the eastern end of the rupture (Karadere-Düzce area), stresses are rotated clockwise. We conclude that the Izmit earthquake caused significant stress partitioning along the rupture. The direction of stress rotation is related to the orientation of the individual fault segments along the NAFZ. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: AFTERSHOCKS; FAULT PLANE SOLUTIONS; NORTH ANATOLIAN FAULT; SEISMOTECTONICS; STRESS TENSOR INVERSION